Relationship of Physical Activities with Nutrition Status in Students at SMK Negeri 1 Percut Sei Tuan Deli Serdang District - Hasnizar; Evawany Aritonang; Etti Sudaryati (Britain International of Exact Sciences (BIoEx) Journal, 2020)
Adolescents are age group that is vulnerable to the nutritional problems. Factors that influence nutritional status in adolescents include physical activity. Physical activity including physical exercise which is one of the efforts to stabilize the intake and expenditure of food substances which is a priority source of energy in the body. The purpose of this study was to analyze the relationship of physical activity with nutritional status in students at SMK Negeri 1 Percut Sei Tuan, Deli Serdang District in 2019. The type of research used was quantitative research with cross sectional research design. The results obtained by the relationship of physical activity with the nutritional status of students p value of 0.003 or smaller than 0.05. The conclusion of the study is that there is a relationship of physical activity with nutritional status in students at SMK Negeri 1 Percut Sei Tuan. Students who are doing physical activity have normal nutritional status because there is a balance between energy intake and expenditure.